Bolivia : Request for Purchase Under the Rapid Financing Instrument-Press Release; Staff Report; and Statement by the Executive Director for Bolivia. (IMF Staff Country Reports; Country Report, 2020)
Bolivia has requested a purchase under the RFI to cover the urgent balance of payments need arising from an ongoing shift in its terms of trade, slowdown in capital flows, and sudden increase in health care expenditure needs, precipitated by the COVID-19 epidemic. Staff assess that Bolivia meets the eligibility requirements for the RFI. Public debt is sustainable, and Bolivia has adequate capacity to repay the Fund.